Novel Encapsulated Herbicide Delivery Mechanism: Its Efficacy in Mimosa Bush (Vachellia farnesiana) Control - Amelia A. Limbongan (MDPI AG, 2021)
Mimosa bush (Vachellia farnesiana) is an invasive woody weed widely distributed in Australia. While it can be controlled using several mechanical and chemical techniques, this study evaluated a novel herbicide delivery mechanism that minimizes the risk of spray drift and potential non-target damage. This method, developed by Bioherbicides Australia, involves the implantation of encapsulated granular herbicides into the stem of intact plants or into the stump after cutting off plants close to ground level (cut stumps). Trials were implemented near Moree (New South Wales, Australia) on intact (two experimental runs) plants and cut stumped (two experimental runs) plants. For each trial, an untreated control plus the conventional basal bark application of a liquid formulation of triclopyr + picloram mixed with diesel was included for comparison. Encapsulated glyphosate, aminopyralid + metsulfuron-methyl, hexazinone and clopyralid were also tested in all trials. In addition, encapsulated triclopyr + picloram, and metsulfuron-methyl were included in one of the intact plant trials. Aminopyralid + metsulfuron-methyl was consistently most effective on cut stump and intact plants, whilst clopyralid provided highest mortality when applied to cut stumps and single-stemmed intact plants. Particularly for multi-stemmed intact plants, clopyralid should be applied to each stem. Overall, the highest efficacy was achieved on single stemmed plants, but with further refinement of the technique, it should be possible to achieve similar results for multi-stemmed individuals. This method resulted in a reduction in the use of herbicide and environmental contamination while significantly improving speed of treatment.